Green strength properties of waterjet abrasive waste as potential composition in green mould By Taguchi And ANOVA approach - Wakhi Anuar, Nur Farah Bazilah; Mohd Khusairi, Muhammad Luqman; Aboo Hassan, Salleh; Marjom, Zolkarnain; Abdul Rasib, Amir Hamzah; Mohd Said, Rahaini (Penerbit Universiti Malaysia Pahang, 2021)
The sand casting process still continues today due to the cost-effectiveness of materials and processes. There is a wide variety of castings related to composition and size, but silica sand is widely available from coastal line mining and has a negative impact on the environment. Moreover, waste from waterjet cutting of non-ferrous and ferrous metals is practically unhazardous and may potentially be used in sand casting mould. The aim of this paper is to optimize the proportion of coal dust, water and bentonite added to the silica sand mixture and the waterjet cutting abrasive waste as a new way of handling waste with the potential to be used in sand casting manufacturing. The method used was L9 orthogonal array optimization and the composition was qualitatively measured using a green compression strength test and a green shear strength test. Factors were evaluated using the analysis of variance (ANOVA) to find the the critical factors while confirmation test was conducted for the optimal material proportion. The study concluded that the ideal ratio for silica sand mixture with waterjet abrasive waste is bentonite-12%, coal dust-5%, and water-7% for green compression strength while bentonite-12%, coal dust-6%, water-7% for green shear strength. With proper selection, the incorporation of waterjet abrasive waste into the green sand mixture is promising to potentially be used in green sand mould casting without undermine the quality of mould.